Scaligerana: Language as a Plot - Andrey V. Golubkov (Studia Litterarum)
The article concentrates on the analysis of Scaligerana, which stood at the origins of the ana tradition, widely represented by works created in the 17th – 19th centuries. The author analyzes the process of creating the text, which is represented by two independent versions (Prima Scaligerana and Secunda Scaligerana), compiled by students and admirers of the philologist Joseph Justus Scaliger, as well as the occuring of the manuscripts, their veneration and the vicissitudes of its publication. The article explores the logic of presenting information about a scholar who appears to the reader as an interlocutor who shares his personal experience and philological research in a private conversation. It demonstrates that the increased interest in the language, etymologies, and interpretations of the “obscurities” is a distinctive feature and the leading plot line of Scaligerana. The article suggests that the reasons for the close attention to language are to be sought in the European linguistic “revolution” of the 16th century, the reasons for which lie in the radical revision of the symbol’s concept that occurred in the Protestant culture with its non-literal interpretation of transubstantiation. The deontologization of language in the absence of a norm, which was established in France only at the end of the 17th century, led to the popularization of the idea of language as the causes of things, which was evidenced by Scaligerana.